Magnetite Core-Shell Nanoparticles in Nondestructive Flaw Detection of Polymeric Materials - Hetti, Mimi; Wei, Qiang; Pohl, Rainer; Casperson, Ralf; Bartusch, Matthias; Neu, Volker; Pospiech, Doris; Voit, Brigitte (ACS Applied Materials and Interfaces, 2016)
Nondestructive flaw detection in polymeric materials is important but difficult to achieve. In this research, the application of magnetite nanoparticles (MNPs) in nondestructive flaw detection is studied and realized, to the best of our knowledge, for the first time. Superparamagnetic and highly magnetic (up to 63 emu/g) magnetite core-shell nanoparticles are prepared by grafting bromo-end-group-functionalized poly(glycidyl methacrylate) (Br-PGMA) onto surface-modified Fe3O4 NPs. These Fe3O4-PGMA NPs are blended into bisphenol A diglycidylether (BADGE)-based epoxy to form homogeneously distributed magnetic epoxy nanocomposites (MENCs) after curing. The core Fe3O4 of the Fe3O4-PGMA NPs endows the MENCs with magnetic property, which is crucial for nondestructive flaw detection of the materials, while the shell PGMA promotes colloidal stability and prevents NP aggregation during curing. The eddy current testing (ET) technique is first applied to detect flaws in the MENCs. Through the brightness contrast of the ET image, surficial and subsurficial flaws in MENCs can be detected, even for MENCs with low content of Fe3O4-PGMA NPs (1 wt %). The incorporation of Fe3O4-PGMA NPs can be easily extended to other polymer and polymer-based composite systems and opens a new and very promising pathway toward MNP-based nondestructive flaw detection in polymeric materials.
CRIS-Team Scopus Importer:2023-03-20
Keywords: atom transfer radical polymerization; magnetic nanocomposites; magnetite nanoparticles; nondestructive flaw detection; poly(glycidyl methacrylate)